Research on Ecosystem Dynamics Based on Lamprey Population Dynamics Model - Kong, Xiangheng; Ma, Chuhan; Liu, Fangxi; Sun, Chen; Sun, Zhijie (Transactions on Environment, Energy and Earth Sciences, 2024)
Adaptive sex ratio variation is a remarkable phenomenon in the biological world. Lampreys are one of the examples. Some researches have shown that the sex ratio of sea lampreys can vary based on external circumstances, and some scholars believe that. the Great Lakes can improve the eco-environment of fish stocks by changing the sex of lampreys. This paper studied the ability for a species to alter its sex ratio depending on resource availability, and provided the resulting interactions in an ecosystem by modeling.Firstly, the paper chose the population dynamics model based on the Lotka-Volterra equation, combined with the dependence of sex ratio on resource availability. Through adjusting model parameters such as predation intensity, symbiosis facilitation intensity, and dynamic rate of change in sex ratio, the paper investigated how changes in lamprey’s sex ratio impact the broader ecosystem. The model results showed that changes in the sex ratio of lampreys induce fluctuations in population dynamics that affect other species that interact with lampreys, thereby altering the structure and stability of the ecosystem.Secondly, we selected the differential equation model of gender differentiation. the paper used partial differential system dynamics equations to describe the dynamic changes in the number of female and male individuals ,used genetic algorithm and genetic models to simulate the evo-lution of genotype frequency and sex ratio, introduced adaptive genes to consider the adaptabil-ity of genotypes in different environments. ,optimized genotype frequency by simulating evolu-tionary process to adapt to changes in external environment by Genetic algorithm, and ana-lyzed the advantages and disadvantages of lampreys’ population according to the results.